Clinical variability in complementary feeding counseling in Türkiye: results from a pediatrician survey - Karabayır, Nalan; Bilgin, Demet Deniz; Başıbüyük, Mine; Büke, Övgü (Frontiers in Pediatrics, 2025)
IntroductionComplementary feeding (CF) is a critical period in infant nutrition, during which pediatricians play a pivotal role. This study aimed to examine CF recommendations by pediatricians in Türkiye, focusing on differences based on infants’ allergy status, and the influence of physician characteristics.MethodsThis cross-sectional study was conducted between September and December 2024 using a semi-structured, self-administered online questionnaire developed by the researchers and distributed among pediatric physicians in Türkiye, including residents, general pediatricians, and subspecialists. For the purposes of this study, allergic infants were defined as those with any form of physician-diagnosed allergy (e.g., atopic dermatitis), excluding confirmed specific food allergies.ResultsAmong 300 pediatric physicians, 90.3% recommended exclusive breastfeeding for the first six months. For non-allergic infants, 87.7% advised initiating CF at six months, compared to 75% for allergic infants. The most commonly recommended initiation method was spoon-fed purées (54.7%), with vegetables being the most frequently suggested first food (61.3%), followed by yogurt (24.3%) and fruit purée (9.3%). Significant differences were observed between allergic and non-allergic infants in the timing of allergenic food introduction. A ≥3-day interval between new foods was more frequently recommended for allergic infants (91.3% vs. 78.3%, p < 0.001). Egg white, egg yolk, and fish were introduced later in allergic infants (p < 0.001), while recommendations for cow's milk and cereals did not differ significantly. Baby-led weaning (BLW) and Baby-Led Introduction to Solids (BLISS) were recommended by 76.7% and 38% of respondents, respectively. Female and less experienced physicians were more likely to endorse infant-led feeding approaches like BLW and BLISS, while more experienced physicians preferred spoon-feeding. Multivariate logistic regression revealed that physician experience and gender were significantly associated with CF method recommendations.DiscussionThese findings indicate that although most pediatricians in Türkiye align with international CF guidelines, notable inconsistencies remain based on infant allergy status and provider characteristics, underscoring the need for standardized and evidence-based training programs.